2015
DOI: 10.1038/srep12641
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Nitrogen Doping in Silicon by Self-Assembled Monolayers

Abstract: This Report presents a nitrogen-doping method by chemically forming self-assembled monolayers on silicon. Van der Pauw technique, secondary-ion mass spectroscopy and low temperature Hall effect measurements are employed to characterize the nitrogen dopants. The experimental data show that the diffusion coefficient of nitrogen dopants is 3.66 × 10−15 cm2 s−1, 2 orders magnitude lower than that of phosphorus dopants in silicon. It is found that less than 1% of nitrogen dopants exhibit electrical activity. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…The MLD method has been expanded to the use of arsenic atoms as n‐type dopants using triallylarsine, methylarsenic acid, or arsenic azide by click chemistry . Recently, the use of nitrogen‐containing precursor molecules has also been reported, since nitrogen atoms have a lower thermal‐diffusion coefficient than phosphorus or boron. This allows for a more accurate annealing process, as longer annealing times, i.e., 1050 °C for 2 min, can be used while still obtaining shallow junctions (<50 nm).…”
Section: Dopingmentioning
confidence: 99%
“…The MLD method has been expanded to the use of arsenic atoms as n‐type dopants using triallylarsine, methylarsenic acid, or arsenic azide by click chemistry . Recently, the use of nitrogen‐containing precursor molecules has also been reported, since nitrogen atoms have a lower thermal‐diffusion coefficient than phosphorus or boron. This allows for a more accurate annealing process, as longer annealing times, i.e., 1050 °C for 2 min, can be used while still obtaining shallow junctions (<50 nm).…”
Section: Dopingmentioning
confidence: 99%
“…A further study showed that if a cap layer is not used, the presence of carbon is much lower, which suggests that the cap layer influences the characteristics of the diffused layer. Nitrogen, an n‐type dopant, has also been explored as an alternative precursor, and a final electrical carrier dose result of 1.4 × 10 11 at cm 2 was obtained . In another work, planar, nanostructured Si was doped using triallyarsine to obtain a carrier concentration of 2 × 10 20 at cm −3 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no literature to report the role of nitrogen co-doping with phosphorus in silicon, in particular for the interaction between two dopants. Our group found that nitrogen dopants retard the electrical activity of phosphorus when co-doped with phosphorus via monolayer doping process [45]. As shown in Figure 7, nitrogen elements were introduced into the silicon surface by Boc-allylamine or P-N bond with phosphorus.…”
Section: A Dopant Elements In Monolayer Dopingmentioning
confidence: 99%
“…However, the actual activation rate evaluated by low temperature Hall measurement is unexpectedly low (~7%) by comparing the electrically active phosphorus dopants with the total phosphorus elements. As our group previously reported [45], nitrogen is one of the factors to retard the activation of phosphorus by forming N-P complex. We believe that the observed low ionization rate is due to nitrogen contamination introduced by coupling reagents (DCC and DMAP) in the reaction process.…”
Section: Dendrimers -Fundamentals and Applicationsmentioning
confidence: 99%